Das Geistige in der Kunst : Von Blauen Reiter zum Abstrakten Expressionismus. - Wiesbaden; Beck, Herbert; Daur, Jörg; Eckelmann, Gerd; Hahl-Fontaine, Jelena; Hoberg, Annegret; Müller, Helmut Georg; Petzinger, Renate; Rattemeyer, Volker (Wiesbaden : Museum Wiesbaden, 2010)
Amiet, Cuno ; Bechtejeff, Wladimir von ; Bloch, Albert ; Burljuk, Vladimir Davidovic ; Campendonk, Heinrich ; Delaunay, Robert ; Delaunay, Sonia ; Derain, André ; Erbslöh, Adolf ; Feininger, Lyonel ; Gottlieb, Adolph ; Hartley, Marsden ; Hofmann, Hans ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Kanolde, Alexander ; Klee, Paul ; Louis, Morris ; Macke, August ; Macke, Helmuth ; Marc, Franz ; Matisse, Henri ; Motherwell, Robert ; Münter, Gabriele ; Newman, Barnett ; Reinhardt, Ad ; Rothko, Mark ; Sacharoff, Alexandr ; de Vlaminck, Maurice ; Werefkin, Marianne von
Exhibition. Das Geistige in der Kunst : Von Blauen Reiter zum Abstrakten Expressionismus,Museum Wiesbaden, Wiesbaden, 2010-10-31. 2011-02-27
boek